Validity Of Marriage And Registration Of Different Religions After The Constitutional Court Decision Number 24/PUU-XX/2022 (Study of Determination Number 155/PDT.P/2023/PN.Jkt.Pst) - Fadilah, Nurul; Harahap, Burhanudin; Purwadi , Hari (PT. Hafasy Dwi Nawasena, 2024)
This study aims to analyze the considerations of the Central Jakarta District Court Determination Number 155/PDT.P/2023/PN.Jkt.Pst which granted the registration of interfaith marriages in the perspective of the Indonesian legal system and its implications for the duties and authority of Notaries. This research is prescriptive with a statutory case approach and case approach method. The legal materials used are primary legal materials and secondary legal materials. The legal material collection technique is done through literature study. The research analysis is done by deductive method. The research found that by ignoring the Constitutional Court decision, in essence, the judge of the Central Jakarta District Court has reduced the position of the Constitutional Court as the guardian of the constitution and the Pancasila ideology. Considering that Pancasila is stated in the Preamble of the 1945 Constitution. Therefore, negating the Constitutional Court decision means the same as negating the Constitution and Pancasila. The Determination of the Central Jakarta District Court Number 155/PDT.P/2023/PN.Jkt.Pst indirectly affects the validity of marriage agreement deeds made by notaries. To avoid legal problems in the future for notaries and the parties involved, notaries must adhere to the principle of caution and provide legal counseling to the parties who will make interfaith marriage agreement deeds before a notary.